Implementation of Annual Budget Performance Contracts and Annual Performance Agreements in the Local Governments: What are the key issues? - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
The Government of Uganda (GoU) introduced a Performance Management Framework aimed at enhancing results oriented management within the Public Service. The main thrust is to empower Accounting Officers to make effective decisions on resources to achieve specified results, and ensure delivery of high quality services and ultimately build confidence and trust. The framework adopted two instruments; Annual Performance Agreements (APA), and Annual Budget Performance Contracts (ABPC). Performance management in Uganda’s Public Service is results-based, aimed at ensuring that organizations and individuals contribute to improved service delivery and the attainment of national development objectives. The key elements of results oriented management are setting output targets, performance indicators, monitoring and evaluation as well as rewards/sanctions. According to the Local Government Performance Assessment, Budget Monitoring and Accountability Unit (BMAU), Ministry of Local Government reports, and the National Delivery Survey Results, 2015 both instruments have not yet delivered the desired performance enhancement, accountability and improvement in service delivery. The reports highlighted several weaknesses thatincluded ineffective implementation of a number of public service reforms, corruption, poor work environment, low motivation and remuneration, and low adoption of ICT. The focus of this policy brief is on implementation of the two instruments as public service reforms by the Accounting Officers in Local Governments. It also gives key issues and recommendations.